The Impact of Women Entrepreneurs in Business Development of Sri Lanka - Jayawardane, V.P.T. (Department of Human Resource Management, University of Sri Jayewardenepura, Nugegoda., 2016)
Women entrepreneurship is a subject of much interest and significance in the world. Recently it has been gaining higher importance in Sri Lanka with the economic changes and globalization. Legislations have been created with laws and by-laws to support motivating entrepreneurship, encouraging education and training for potential entrepreneurs; which in return has contributed towards the empowerment of women. Literature confirms that there are many successful stories of female business entrepreneurs in Sri Lanka. As observed in countries like Japan and Spain, the development and nurturing of women entrepreneurs would be a value addition to the development and prosperity of the whole country. Many women leave their respective employment for various reasons. Such women can be encouraged to be entrepreneurs who will contribute to the income of their family as well as the development of the country. This will even construct a significant shift in the demographic characteristics of business and economic growth of Sri Lanka. Women entrepreneurs provide a strong, empathetic and supportive role in the society. All these reasons, created the motivation for the researcher to study this area. This article intends to identify the various issues and challenges faced by women entrepreneurs of Sri Lanka, the competencies they exercise to overcome them and to find out whether the women entrepreneurs have made an impact on the development of Sri Lanka. This research was undertaken using qualitative methodology in a chosen sample of 22 women entrepreneurs. In conclusion the outcomes identified that the women entrepreneurs were highly capable in motivating employees, retaining customers, creating job opportunities and they invested most of their earnings for the betterment of their family. The study will reemphasise the importance of women entrepreneurs who transform families and society, while making contributions to the business development of Sri Lanka.
Keywords: Women Entrepreneurs; Competencies; Business Development; Sri Lanka